Comparison of Preparation Methods of Copper Based PGMFree Diesel-Soot Oxidation Catalysts - Ram Prasad; V. R. Bella (Bulletin of Chemical Reaction Engineering & Catalysis, 2011)
CuO-CeO2 systems have been proposed as a promising catalyst for low temperature diesel-soot oxidation. CuO-CeO2 catalysts prepared by various methods were examined for air oxidation of the soot in a semi batch tubular flow reactor. The air oxidation of soot was carried out under tight contact with soot/catalyst ratio of 1/10. Air flow rate was 150 ml/min, soot-catalyst mixture was 110 mg, heating rate was 5 0C/min. Prepared catalysts were calcined at 500 0C and their stability was examined by further heating to 800 0C for 4 hours. It was found that the selectivity of all the catalysts was nearly 100% to CO2 production. It was observed that the activity and stability of the catalysts greatly influenced by the preparation methods. The strong interaction between CuO and CeO2 is closely related to the preparation route that plays a crucial role in the soot oxidation over the CuO-CeO2 catalysts. The ranking order of the preparation methods of the catalysts in the soot oxidation performance is as follows: sol-gel > urea nitrate combustion > Urea gelation method > thermal decomposition > co-precipitation. © 2011 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)